PENGARUH PENYULUHAN METODE SOKRATIK DAN DIDAKTIK DENGAN MEDIA FRUVEBLE CARD TERHADAP PENGETAHUAN DAN SIKAP KONSUMSI BUAH DAN SAYUR PADA ANAK - Junitasari, Helen; Darwis, Darwis; Ningsih, Lisma (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2021)
Obesity and the incidence of fruit and vegetable consumption are experienced by many elementary school children. The lack of consumption of fruits and vegetables is related to the poor metabolic processes in the body, causing obesity and even obesity in children. The purpose of this study was to determine the consumption of fruits and vegetables in elementary school children, the influence of socratic and didactic methods using fruveble card media on knowledge and attitudes about fruit and vegetable consumption in elementary school children. This study used an experimental design with a two-group pre-test post-test research design. The population was 178,196 people with the intervention group of SDN 18 totaling 33 people and the control group of SDN 34 totaling 33 people. Sampling using the total sampling technique. Analyzed through wilcoxon and mann whitney tests. The results of this study also showed that there was an influence on increasing the knowledge score and attitudes of students who were given socratic and didactic method counseling with p value = 0.000 < 0.05. It is hoped that this research can be developed again with a combination of innovative learning methods that arouse more interest in learning so that the knowledge and attitudes of elementary school children about fruit and vegetable consumption can increase. Keywords: Socratic & Didactic, Consumption, Knowledge, Attitude, Fruveble Card